Nudging Human Behaviour towards Sustainability Practices: A Systematic Review - Mohanty, Atasi; Devika; Mohanty, Aashish (Journal of Behavioral Economics and Policy, 2025)
Nudges can be defined as any factor that influences an individual’s behaviour in a predictable way, without removing the choices available to them. Over the past decade, nudging has emerged as a prominent behavioural policy tool. Different types of nudges and how they are used to increase sustainable behaviours in individuals are widely explored in contemporary studies. However, a consolidated understanding of the effectiveness of these nudges and the role of individual differences remains limited. The current study conducted a systematic review of relevant publications on nudges using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search across multiple databases was conducted and 27 empirical studies that met the predefined eligibility criteria were included in the final review. The results indicated the presence of various nudges including default, digital, emotional, informational, norm-based and promotional nudges, which were effective in nudging human behaviour towards sustainable practices. Nudges can also influence decision-making regarding various choices presented by the choice architecture. The influence of personality traits on the effectiveness of nudges was also observed. The study highlights the potential of nudges in promoting sustainable behaviours while also emphasizing the need to consider individual differences in the design of nudging strategies.